\(\dfrac{\dfrac{3}{5}.7^2-3.5^6+\dfrac{3}{5}.3^9}{\dfrac{3}{4}.7^2-\...">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

1 tháng 12 2024

\(\dfrac{\dfrac{3}{5}.7^2-3.5^6+\dfrac{3}{5}.3^9}{\dfrac{3}{4}.7^2-\dfrac{3}{4}.5^7+\dfrac{3}{4}.3^9}\)

\(=\dfrac{\dfrac{3}{5}.7^2-3.5^6+\dfrac{3}{5}.3^9}{\dfrac{5}{4}\left(\dfrac{3}{5}.7^2-3.5^6+\dfrac{3}{5}.3^9\right)}\)

\(=\dfrac{1}{\dfrac{5}{4}}\)

\(=\dfrac{4}{5}\)

26 tháng 7 2018

a. = \(\dfrac{-1}{24}-\left\{\dfrac{1}{4}-\dfrac{-3}{8}\right\}\)

= \(\dfrac{-1}{24}-\left\{\dfrac{1}{4}+\dfrac{3}{8}\right\}\)

= \(\dfrac{-1}{24}-\dfrac{5}{8}\)

= \(\dfrac{-2}{3}\)

b. = \(12\dfrac{7}{88}-3\dfrac{5}{11}\)

= \(8\dfrac{5}{8}\)

c. = \(\dfrac{-28}{9}+\dfrac{-413}{9}\)

= \(-49\)

d. = \(\dfrac{8}{35}:\dfrac{2}{11}+\dfrac{-8}{35}:\dfrac{2}{11}\)

= \(\dfrac{2}{11}:\left(\dfrac{8}{35}+\dfrac{-8}{35}\right)\)

= 0

21 tháng 12 2017

\(\dfrac{4}{9}:\left(\dfrac{-1}{7}\right)+6\dfrac{5}{9}.\left(\dfrac{2}{3}\right)\)

\(=\dfrac{4}{9}.\left(-7\right)+\dfrac{59}{9}.\dfrac{2}{3}\)

\(=\dfrac{2}{9}.\left(-14\right)+\dfrac{2}{9}.\dfrac{59}{3}\)

\(=\dfrac{2}{9}.\left(-14+\dfrac{59}{3}\right)\)

\(=\dfrac{2}{9}.\dfrac{17}{3}\)

\(=\dfrac{34}{27}\)

\(\left(\dfrac{-1}{3}\right)^2.\dfrac{4}{11}+\dfrac{7}{11}.\left(\dfrac{-1}{3}\right)^2\)

\(=\dfrac{1}{9}.\dfrac{4}{11}+\dfrac{7}{11}.\dfrac{1}{9}\)

\(=\dfrac{1}{9}.\left(\dfrac{4}{11}+\dfrac{7}{11}\right)\)

\(=\dfrac{1}{9}.1=\dfrac{1}{9}\)

21 tháng 12 2017

~ \(\dfrac{4}{9}:\left(-\dfrac{1}{7}\right)+6\dfrac{5}{9}.\dfrac{2}{3}\)
\(=\dfrac{4}{9}.\left(-7\right)+\dfrac{59}{9}.\dfrac{2}{3}\)
\(=-\dfrac{28}{9}+\dfrac{118}{27}\)
\(=-\dfrac{84}{27}+\dfrac{118}{27}\)
\(=\dfrac{34}{27}\)
~ \(\left(-\dfrac{1}{3}\right)^2.\dfrac{4}{11}+\dfrac{7}{11}.\left(-\dfrac{1}{3}\right)^2\)
\(=\left(-\dfrac{1}{3}\right)^2.\left(\dfrac{4}{11}+\dfrac{7}{11}\right)\)
\(=\dfrac{1}{9}.\dfrac{11}{11}\)
\(=\dfrac{1}{9}.1\)
\(=\dfrac{1}{9}\)

19 tháng 6 2018

8)\(\frac{4}{9}:\left(-\frac{1}{7}\right)+6\frac{5}{9}:\left(-\frac{1}{7}\right)\)

=\(\frac{4}{9}:\left(-\frac{1}{7}\right)+\frac{59}{9}:\left(-\frac{1}{7}\right)\)

=\(\left(\frac{4}{9}+\frac{59}{9}\right).\left(-7\right)\)

=7.(-7)

=-49

19 tháng 11 2018

5) \(\left(-2\right)^2+\sqrt{36}-\sqrt{9}+\sqrt{25}\)

=\(4+6-3+5\)

=\(12\)

19 tháng 11 2018

2) \(\dfrac{11}{25}.\left(-24,8\right)-\dfrac{11}{25}.75,2\)

=\(\dfrac{11}{25}.\left(-24,8-75,2\right)\)

=\(\dfrac{11}{25}.\left(-100\right)\)

=\(-44\)

5 tháng 11 2017

a) \(\dfrac{1}{4}+\left(-\dfrac{3}{8}\right)=\dfrac{2}{8}+\left(-\dfrac{3}{8}\right)=-\dfrac{1}{8}\)
b)\(\dfrac{2^{10}.3^4}{3^5.2^8}=\dfrac{2^8.2^2.3^4}{3^4.3.2^8}=\dfrac{2^2}{3}=\dfrac{4}{3}\)
c) \(0,5.\sqrt{100}-\sqrt{\dfrac{1}{9}}=\dfrac{5}{10}.10-\dfrac{1}{3}=5-\dfrac{1}{3}=\dfrac{15}{3}-\dfrac{1}{3}=\dfrac{14}{3}\)
d) \(4\dfrac{5}{9}:\left(-\dfrac{5}{7}\right)+5\dfrac{4}{9}:\left(-\dfrac{5}{7}\right)\)
\(=\dfrac{41}{9}:\left(-\dfrac{5}{7}\right) +\dfrac{49}{9}:\left(-\dfrac{5}{7}\right)\)
\(=\left(\dfrac{41}{9}+\dfrac{49}{9}\right):\left(-\dfrac{5}{7}\right)\)
\(=\dfrac{90}{9}:\left(-\dfrac{5}{7}\right)\)
\(=10:\left(-\dfrac{5}{7}\right)\)
\(=10.\left(-\dfrac{7}{5}\right)\)
\(=-14\)

21 tháng 7 2018

*Trả lời :

a) \(-\dfrac{3}{4}.5\dfrac{3}{13}-0,75.\dfrac{36}{13}\)

= \(-\dfrac{3}{4}.\dfrac{68}{13}-\dfrac{3}{4}.\dfrac{36}{13}\)

=\(\dfrac{3}{4}.\dfrac{-68}{13}-\dfrac{3}{4}.\dfrac{36}{13}\)

=\(\dfrac{3}{4}.\cdot\left(\dfrac{-68}{13}-\dfrac{36}{13}\right)\)

=\(\dfrac{3}{4}.\left(-8\right)\)

= \(-6\)

b)\(4\dfrac{5}{9}:\left(-\dfrac{5}{7}\right)+\dfrac{49}{9}:\left(-\dfrac{5}{7}\right)\)

=\(\dfrac{41}{9}-\left(-\dfrac{5}{7}\right)+\dfrac{49}{9}:\left(-\dfrac{5}{7}\right)\)

=\(\left(\dfrac{41}{9}+\dfrac{49}{9}\right):\left(-\dfrac{5}{7}\right)\)

=\(\dfrac{90}{9}:\left(-\dfrac{5}{7}\right)\)

=\(10:\left(-\dfrac{5}{7}\right)\)

=\(-14\)

c)\(\left(-\dfrac{3}{5}+\dfrac{4}{9}\right):\dfrac{7}{11}+\left(-\dfrac{2}{5}+\dfrac{5}{9}\right):\dfrac{7}{11}\)

=\(\left(-\dfrac{3}{5}\right)+\dfrac{4}{9}:\dfrac{7}{11}+\left(-\dfrac{2}{5}\right)+\dfrac{5}{9}:\dfrac{7}{11}\)(áp dụng tính chất phá ngoặc )

=\(\left\{\left[-\dfrac{3}{5}+\left(-\dfrac{2}{5}\right)\right]+\left(\dfrac{4}{9}+\dfrac{5}{9}\right)\right\}:\dfrac{7}{11}\)

=\(\left(-\dfrac{5}{5}+\dfrac{9}{9}\right):\dfrac{7}{11}\)

=\(\left(-1+1\right):\dfrac{7}{11}\)

\(=0:\dfrac{7}{11}\)

=0.

d)\(\dfrac{6}{7}:\left(\dfrac{3}{26}-\dfrac{3}{13}\right)+\dfrac{6}{7}:\left(\dfrac{1}{10}-\dfrac{8}{5}\right)\)

=\(\dfrac{6}{7}:\left[\dfrac{3}{26}+\left(-\dfrac{6}{26}\right)\right]+\dfrac{6}{7}:\left[\dfrac{1}{10}+\left(-\dfrac{16}{10}\right)\right]\)

=\(\dfrac{6}{7}:\left(-\dfrac{3}{26}\right)+\dfrac{6}{7}:\left(-\dfrac{3}{2}\right)\)

=\(\dfrac{6}{7}:\left[\left(-\dfrac{3}{26}\right)+\left(-\dfrac{39}{26}\right)\right]\)

=\(\dfrac{6}{7}:\left(-\dfrac{21}{13}\right)\)

=\(-\dfrac{26}{49}\)

16 tháng 10 2017

Lời giải :

a ) \(1\dfrac{4}{23}+\dfrac{5}{21}-\dfrac{4}{23}+0,5+\dfrac{16}{21}\)

\(=\left(1\dfrac{4}{23}-\dfrac{4}{23}\right)+\left(\dfrac{5}{21}+\dfrac{16}{21}\right)+0,5\)

\(=2,5\)

b ) \(\dfrac{3}{7}.19\dfrac{1}{3}-\dfrac{3}{7}.33\dfrac{1}{3}\)

\(=\dfrac{3}{7}\left(19\dfrac{1}{3}-33\dfrac{1}{3}\right)\)

\(=\dfrac{3}{7}\left(19-33\right)\)

\(=\dfrac{3}{7}\left(-14\right)\)

\(=-6\)

c ) \(9\left(-\dfrac{1}{3}\right)^3+\dfrac{1}{3}\)

\(=9\left(-\dfrac{1}{27}\right)+\dfrac{1}{3}\)

\(=-\dfrac{1}{3}+\dfrac{1}{3}\)

\(=0\)

d ) \(15\dfrac{1}{4}\div\left(-\dfrac{5}{7}\right)-25\dfrac{1}{4}\div\left(-\dfrac{5}{7}\right)\)

\(=\left(15\dfrac{1}{4}-25\dfrac{1}{4}\right)\div\left(-\dfrac{5}{7}\right)\)

\(=-10\left(-\dfrac{7}{5}\right)\)

\(=14\)

11 tháng 11 2018

a)= \(\left(\dfrac{4}{9}-\dfrac{17}{18}\right)+\left(\dfrac{17}{14}-\dfrac{5}{7}\right)+\dfrac{11}{125}\)

= \(\dfrac{-1}{2}\) + \(\dfrac{1}{2}\) + \(\dfrac{11}{125}\)

= 0 + \(\dfrac{11}{125}\)

= \(\dfrac{11}{125}\)

b) \(=\left(1-1\right)+\left(\dfrac{-1}{2}-\dfrac{1}{2}\right)+\left(2-2\right)\) +

\(\left(\dfrac{-2}{3}-\dfrac{1}{3}\right)+\left(3-3\right)+\left(\dfrac{-3}{4}-\dfrac{1}{4}\right)\) + 4

= 0 + (-1) + 0 + (-1) + 0 + (-1) + 4

= -1

c) = \(\dfrac{1}{3}.\dfrac{14}{25}-\dfrac{1}{2}.\dfrac{14}{25}\)

= \(\dfrac{14}{25}.\left(\dfrac{1}{3}-\dfrac{1}{2}\right)\)

= \(\dfrac{14}{25}.\left(\dfrac{-1}{6}\right)\)

= \(\dfrac{-7}{75}\)

d) = \(\left(\dfrac{3}{7}+\dfrac{4}{7}\right)+\left(\dfrac{5}{13}-\dfrac{18}{13}\right)\)

= 1 + (-1)

= 0

25 tháng 12 2017

Tính 1 câu thoy nhé !

\(\dfrac{3}{7}.19\dfrac{1}{3}-\dfrac{3}{7}.33\dfrac{1}{3}\)

= \(\dfrac{3}{7}.\left(19\dfrac{1}{3}-33\dfrac{1}{3}\right)\)

=\(\dfrac{3}{7}.-14=-6\)

26 tháng 11 2022

a: \(=\dfrac{-3}{4}\left(31+\dfrac{11}{23}+8+\dfrac{12}{23}\right)=\dfrac{-3}{4}\cdot40=-30\)

b: \(=\left(\dfrac{7}{3}+\dfrac{7}{2}\right):\left(-\dfrac{25}{6}+\dfrac{22}{7}\right)+\dfrac{15}{2}\)

\(=\dfrac{35}{6}:\dfrac{-175+132}{42}+\dfrac{15}{2}\)

\(=\dfrac{35}{6}\cdot\dfrac{42}{-43}+\dfrac{15}{2}\)

\(=\dfrac{35\cdot7}{-43}+\dfrac{15}{2}\)

\(=\dfrac{-70\cdot7+15\cdot43}{86}=\dfrac{155}{86}\)

c: \(=\dfrac{-7}{5}\left(4+\dfrac{5}{9}+5+\dfrac{4}{9}\right)=\dfrac{-7}{5}\cdot10=-14\)

d: \(=4+\dfrac{25}{16}+25\cdot\left(\dfrac{9}{16}\cdot\dfrac{64}{125}\cdot\dfrac{-8}{27}\right)\)

\(=\dfrac{89}{16}+25\cdot\dfrac{-32}{375}\)

\(=\dfrac{89}{16}-\dfrac{32}{15}=\dfrac{823}{240}\)

e: \(=\dfrac{2}{3}-4\cdot\left(\dfrac{2}{4}+\dfrac{3}{4}\right)=\dfrac{2}{3}-5=-\dfrac{13}{3}\)